Primerjalna analiza in predlog obdelave preostalih mešanih komunalnih odpadkovna primeru ljubljanske regije - Malus, Marta (Gradbeni vestnik, 2010)
Because of the legislation demands and increasingly diflicult and expensive way to provide the landfill space, MBT (mechanical-biological treatment) of the residual mixed municipal waste is foreseen for the Ljubljana region. The analysis of possible treatments for residual mixed municipal waste and analysis of chosen treatments are presented. The chosen treatments are analysed from the principles of sustainable development. On the basis of comparative analysis, a proposition of preferential procedure is suggested. The chosen treatments are analyseli and compared from the environmental point of view and also from economic and sociological point of view. The treatment process recently suggested by Snaga is also taken into considoration. The analyses, which are presented in this paper, were made completely separately from those made by Snaga. The proposition of preferential treatment consists of sorting-out the recyclables, mechanical separatian of the lighter, caloric fraction to be usod as a solid recovered fuel, whereas the residual heavy fraction (which contains the concentrated biodegradable components) is prepored and utilised in on anaerobic digestion with the production of biogas and the dehydration of the sludge before disposal.
Keywords: ecology; ekologija; komunalni odpadki; ravnanje z odpadki